RETRACTED: Nutrition of frequently ill preschool children in organized collectives - Akhmadaliyeva N.O.; Salomova F.I.; Sadullayeva Kh.A.; Abdukadirova L.K.; Imamova A.O. (BIO Web of Conferences, 2024)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001